Sex- and age-specific association between outdoor light at night and obesity in Chinese adults: A national cross-sectional study of 98,658 participants from 162 study sites - Zhang, Xiaoyun; Zheng, Ruizhi; Xin, Zhuojun; Zhao, Zhiyun; Li, Mian; Wang, Tiange; Xu, Min; Lu, Jieli; Wang, Shuangyuan; Lin, Hong; Wang, Weiqing; Ning, Guang; et al. (Frontiers in Endocrinology, 2023)
Background: Exposure to light at night (LAN) is a potent disruptor of the circadian system. Whether LAN exposure exerts a sex- or age-specific influence on obesity needs investigation. Objectives: To estimate the sex- and age-specific associations of exposure to outdoor LAN and obesity based on a national and cross-sectional survey. Methods: The study included a nationally representative sample of 98,658 adults aged ≥ 18 years who had lived in their current residence for ≥ 6 months from 162 study sites across mainland China in 2010. Outdoor LAN exposure was estimated from satellite imaging data. General obesity was defined as body-mass index (BMI) ≥ 28 kg/m2 and central obesity was defined as waist circumference ≥ 90 cm in men and ≥ 85 cm in women. Linear and logistic regression models were used to examine the associations between LAN exposure and prevalent obesity in sex and age categories. Results: A monotonically increasing association of outdoor LAN with BMI, waist circumference was observed in all sex and age categories, except for adults aged 18-39 years. Significant associations of LAN exposure with prevalent obesity were observed in each sex and age category, especially in men and older people. Per 1-quintile increase in LAN was associated with 14% increased odds of general obesity in men (odds ratio, OR=1.14, 95% confidence interval, CI=1.07-1.23) and 24% in adults aged ≥ 60 years (OR=1.24, 95% CI=1.14-1.35). Per 1-quintile increase in LAN was associated with 19% increased odds of central obesity in men (OR=1.19, 95% CI=1.11-1.26) and 26% in adults aged ≥ 60 years (OR=1.26, 95% CI=1.17-1.35). Conclusions: Increased chronic outdoor LAN exposure was associated with increased prevalence of obesity in sex- and age- specific Chinese populations. Public health policies on reducing light pollution at night might be considered in obesity prevention.